Analysis of the Factors Affecting Changes in Land Cover Patterns in Rural Districts in East of Guilan Province (Iran) for Foresight - Taleshi, Mostafa; Afrakhteh, Hassan; Nejad, Mohammad Ali Rahimipour Sheikhani (Review of Environment and Earth Sciences, 2017)
Foresight is among the key topics in natural resource protection for sustainability of rural settlement system. In foresight of land cover evolutions, identification of factors affecting the evolutions is of paramount importance. In the present research, in order to undertake foresight and sustainable land planning in rural districts in East of Guilan as a special ecologic zone encompassing 744 villages, principle variables were collected via a questionnaire using Delphi method with the help pf experts, followed by calculation of significance factors. A total of 93 variables were found to affect the changes in land cover within the study area at local, regional and national scales. Among these, key variables were identified utilizing MIC-MAC Software. In order to develop scenarios by a 20-member expert panel, 19 key drivers of the changes in land cover were homogenized and 9 primary descriptor were defined. For each descriptor, three variant qualitative component were prepared, which described all possible cases from the most critical case to the most desired one. In the next stage, with the help of cross-impact balance matrix and Monte Carlo simulations in Scenario Wizard Software, a total of three scenarios with 15-year horizons were obtained based on maximum consistency. Finally, based on the maximal effectiveness on protection of natural land cover and continuation of sustainability, the obtained scenarios were designated as balanced ecologic changes, relatively balanced ecologic changes, and imbalanced ecologic changes.